A Study on the Relationship Between Preservice STEM Teachers’ Beliefs About Migrant Students and Teachers’ Roles in Chinese Urban Schools - Wang, Jingying; Yang, Mingyue (Education and urban society, 2021)
The survival and development of migrant students in urban areas were always the focus of all sectors of society. Science, technology, engineering, and mathematics (STEM) subjects are most likely to cause learning difficulties for migrant students, and the beliefs of STEM teachers about migrant students and their role closely affect classroom teaching and after-school support and tutoring. This study focuses on 268 STEM-oriented preservice teachers majoring in elementary education in a normal university in Beijing, China. A questionnaire investigation has been conducted on their beliefs about migrant students’ and teachers’ role in urban elementary schools with metaphor method. The results show that there are significant differences among all the preservice STEM teachers at grade levels, and most of them hold the reality of development and the possibility of development beliefs about migrant students, and the facilitating orientation beliefs about teachers’ role as well. Grade factors are influenced by their curriculum, and beliefs about migrant students show an excessive trend from existence orientation to development orientation with the increasing grade levels. There is a significant correlation between beliefs about migrant students’ and teachers’ role, and preservice teachers with the reality of development beliefs about students are more inclined to the facilitating orientation beliefs about teachers’ role.